TINGKAT KEMAMPUAN TENDANGAN SABIT PADA PERGURUAN PENCAK SILAT SETIA HATI TERATE (PSHT) RAYON BALONGASEM KECAMATAN LENGKONG KABUPATEN NGANJUK - Kustoro, Arif; Sinto Raya, Garnika Ade (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2024)
The sickle kick is one of the most important kick techniques in pencak silat. This study aims to examine the level of sickle kick ability among members of the Setia Hati Terate Pencak Silat College (PSHT) Balongasem Rayon, Lengkong District, Nganjuk Regency. One of the kicking techniques that is often used in attacks is the sickle kick. In this case, a survey conducted on the ability of sickle kicks in the training of Balongasem Rayon athletes, Lengkong District, Nganjuk Regency was attended by 18 participants. The type of research used isiquantitative with survey methods. Instrumentitest using testi speedi kick isickle Results Research shows that in the